2020
DOI: 10.1021/acs.organomet.0c00378
|View full text |Cite
|
Sign up to set email alerts
|

High Lewis Acidity at Planar, Trivalent, and Neutral Bismuth Centers

Abstract: Geometric perturbation away from classical structures can engender unusual frontier MO situations leading to high Lewis acidity. Recently we reported a T-shaped bismuth triamide, which exhibited planar Lewis acidity that was unprecedented for neutral group 15 compounds. We now report a comprehensive computational assessment of the origins of planar Lewis acidity in such compounds. We subsequently use several metrics such as MO energies, the Global Electrophilicity Index, ligand coordination strengths, and fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 102 publications
3
25
0
Order By: Relevance
“…Trianionic pincer-type ligands are well-known supporting structures within transition-metal organometallic chemistry, and their ability to enforce constrained geometries has likewise found applications in main-group chemistry. Within this vein, we have reported the preparation of the phosphorus compound 1 based on the trianionic N , N , N -chelate {N­[ o -NMe-C 6 H 4 ] 2 } 3– , which adopts a nontrigonal local geometry about phosphorus as a function of the ring constraints (Figure , top). , Whereas the reaction of phosphorus­(III) amides with protic pronucleophiles commonly leads to phosphitylation by metathetical exchange, , compound 1 undergoes intermolecular oxidative addition of amine N–H and alcohol O–H bonds to give pentacoordinate σ 5 -P adducts 1 ·[H]­[E] (E = OR, NHR). In situ spectroscopy demonstrated that the observed oxidative addition reactions proceed via a stepwise mechanism involving initial E–H bond cleavage by phosphorus-ligand cooperation, followed by subsequent intramolecular σ 3 -P → σ 5 -P tautomerism (Figure , top).…”
Section: Introductionsupporting
confidence: 86%
“…Trianionic pincer-type ligands are well-known supporting structures within transition-metal organometallic chemistry, and their ability to enforce constrained geometries has likewise found applications in main-group chemistry. Within this vein, we have reported the preparation of the phosphorus compound 1 based on the trianionic N , N , N -chelate {N­[ o -NMe-C 6 H 4 ] 2 } 3– , which adopts a nontrigonal local geometry about phosphorus as a function of the ring constraints (Figure , top). , Whereas the reaction of phosphorus­(III) amides with protic pronucleophiles commonly leads to phosphitylation by metathetical exchange, , compound 1 undergoes intermolecular oxidative addition of amine N–H and alcohol O–H bonds to give pentacoordinate σ 5 -P adducts 1 ·[H]­[E] (E = OR, NHR). In situ spectroscopy demonstrated that the observed oxidative addition reactions proceed via a stepwise mechanism involving initial E–H bond cleavage by phosphorus-ligand cooperation, followed by subsequent intramolecular σ 3 -P → σ 5 -P tautomerism (Figure , top).…”
Section: Introductionsupporting
confidence: 86%
“…Upon 2 nd order mixing, the ptype orbital originating from the 2e set can interact with additional orbitals of p-symmetry, thereby allowing for ne tuning of the electronic structure upon pincer ligand derivatization. 35 If the LUMO is sufficiently lowered by geometrical constraints, reduction affording a Pn(I) complex can occur, as initially proposed for I (electromorphism), which is generated upon addition of PCl 3 to the diketone precursor. 20,21 DFT computations by Sakaki show that, within the Kohn-Sham frontier orbitals, two phosphorus lone pairs can be located with respective p-type and sp-hybrid character.…”
Section: Effects Of Geometric Perturbation On Bondingmentioning
confidence: 93%
“…Furthermore, our findings demonstrate the moderate Lewis acidity of BiCl 3 in contrast to highly Lewis acidic bismuthenium cations or neutral bismuth triamides, as outlined by several recent experimental and computational investigations. 99 104 …”
Section: Results and Discussionmentioning
confidence: 99%